The effect of 20 repetitions badminton footwork training on increasing maximum oxygen volume (VO2Max) - I Putu Astrawan; I Made Dhita Prianthara; I A Pascha Paramurthi (Physical Education Departement of University PGRI Jombang, 2025)
Footwork is foot movements that regulate the body to position the body in such a way that makes it easier to make the movement to hit the shuttlecock according to its position. The type of quasi-experimental research with the design used in this research is